Erodibility of fluidized cohesive sediments in unidirectional open flows. (15th January 2017) - Zhang, Minxi; Yu, Guoliang; La Rovere, Andrea; Ranzi, Roberto
Abstract: In this study, the erodibility of fluidized cohesive sediments from the seabed of Hangzhou Bay, China, was experimentally investigated in unidirectional open flows. The results indicated that the yield stress is a major factor influencing the erodibility of cohesive sediments. As the yield stress increases, the critical Shields parameter, critical velocity, and critical shear stress increase, but the scour rate decreases. However, a lower yield stress of sediment indicates higher potential of being eroded. Furthermore, the equation for the critical condition of sediment motion, as well as the equation for the scour rate, without considering the degree of fluidization of sediments, may have limited application ranges. Hence, the bed shear stress, critical shear stress, and yield stress should be considered to predict the scour rate. Finally, a modified empirical equation based on the Partheniades (1962) equation is proposed by introducing the yield stress, which is a rheological parameter, in order to calculate the scour rate of cohesive sediments. Highlights: Yield stress is a major factor influencing the erodibility of cohesive sediment. A lower yield stress for fluidized cohesive sediments enhances sediment erosion. A modified scour rate formula as a function of yield stress is proposed.